2017
DOI: 10.18632/oncotarget.14797
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the neutrophil-to-lymphocyte ratio in the ARQ 197-215 second-line study for advanced hepatocellular carcinoma

Abstract: The ARQ 197-215 study randomized patients to tivantinib or placebo and pre-specified efficacy analyses indicated the predictive value of MET expression as a marker of benefit from tivantinib in hepatocellular carcinoma (HCC). We aimed to explore the neutrophil-to-lymphocyte ratio (NLR) in 98 ARQ 197-215 patients with available absolute neutrophil count and absolute lymphocyte count at baseline. The cut-off value used to define high versus low NLR was 3.0. In univariate analysis, high NLR was associated with ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…During the writing of this manuscript, exploratory analyses from two prospective studies performed in patients with advanced HCC have been published: Personeni et al analysed the prognostic value of NLR in patients treated in the ARQ 197–215 study, a randomised placebo-controlled study testing the MET inhibitor tivantinib in the second line setting for patients with advanced HCC [ 30 ]. Multivariate analysis revealed that baseline NLR was an independent prognostic biomarker in this setting; NLR >3 was associated with poorer survival (HR1.65; 95% CI 1.05; 2.59; p = 0.03) [ 30 ]. Bruix et al conducted a pooled exploratory analysis from the 2 landmark placebo-controlled phase 3 studies (SHARP and Asia-Pacific) in an attempt to identify prognostic factors for OS and predictive factors of sorafenib benefit [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the writing of this manuscript, exploratory analyses from two prospective studies performed in patients with advanced HCC have been published: Personeni et al analysed the prognostic value of NLR in patients treated in the ARQ 197–215 study, a randomised placebo-controlled study testing the MET inhibitor tivantinib in the second line setting for patients with advanced HCC [ 30 ]. Multivariate analysis revealed that baseline NLR was an independent prognostic biomarker in this setting; NLR >3 was associated with poorer survival (HR1.65; 95% CI 1.05; 2.59; p = 0.03) [ 30 ]. Bruix et al conducted a pooled exploratory analysis from the 2 landmark placebo-controlled phase 3 studies (SHARP and Asia-Pacific) in an attempt to identify prognostic factors for OS and predictive factors of sorafenib benefit [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the authors observed that a baseline high NLR (greater than 3) is an independent prognostic biomarker in patients with HCC who are candidate for second-line treatments. An important finding was that for overall survival, no interaction was detected between NLR status and treatment [ 36 ]. These results confirm that NLR have a prognostic value regardless the treatment applied.…”
Section: Discussionmentioning
confidence: 99%
“…Initial tumor biomarker analysis from this study showed the prognostic value and the predictive value of MET expression as a marker of benefit from tivantinib [ 25 ]. Further biomarker analyses from the same study suggested that tumor MET levels were higher in patients previously treated with sorafenib, circulating biomarkers such as MET and HGF might be prognostic in second-line HCC [ 26 ], and baseline neutrophil-to-lymphocyte ratio was an independent prognostic biomarker [ 27 ]. Based on the phase 2 results, tivantinib has been evaluated in two phase 3 trials in previously treated patients with high tumor MET expression, the METIV-HCC trial in western countries [ 21 ], and the JET-HCC trial in Japan [ 22 ].…”
Section: Negative Studies For Second-line Treatment Of Hccmentioning
confidence: 99%